Case Reports of Five Cancer Patients with Unusual Course - Payrhuber, Dietmar; Thieves, Karin; Sangaletti, Piero; Muehlmann, Josef; Frass, Michael (Homeopathy, 2018)
Introduction The analysis of the periodic table of elements by Jan Scholten opened the way for a new kind of classification and repertorisation of homeopathic remedies. Thereby, group analysis (resorting to series and stages) makes precise prescriptions possible. This approach appears to yield striking results, even in severe cases. Whereas Hahnemann stressed the emotional state (‘Gemüthssymptome’, Organon § 210) when choosing a remedy, Scholten 200 years later investigated the mental picture that represents a life conflict or even a life theme that may maintain the disease process. The person's environment, emotional traumas or a conflict drives him or her to suppress and dissect painful emotions. Such compensations can become subconscious and so strong that they can no longer be controlled; they then influence the patient with a highly destructive energy.Methods We present five case reports, each dealing with an unusual clinical course of severe cancer associated with homeopathic treatment using the Scholten method.Results By presenting these cases, we consider how the constitution (lifelong signs and symptoms of the patient) and the mental state are interwoven and, as a complex mechanism, might provoke disease.Conclusion The appropriate homeopathic remedy, reflecting the Scholten approach, seemed to have beneficial impact on the disease process of the five individuals presented.
Keywords: cancer; life theme; hairy cell leukaemia; non-Hodgkin lymphoma; stomach cancer; breast cancer; pleural mesothelioma